Mating sanctuary for whitespotted eagle rays (Aetobatus narinari) in Brazilian southeastern waters - Karlovic, Thamíris C.; Longo, Gabriela R.; Lopes, Arielly R.; Amaral, Iara L.; Yoshino, Yara A.; Almeida, Amanda A. V.; Andrade, Lucas S.; Bedin, Felipe G.; de Abreu, Marcos T.; Chioatto, Francesco S. M.; Kian, Carolina Y.; Candido, Lucas C.; et al. (FapUNIFESP (SciELO), 2024)
This article provides the first records of courtship behavior and a mating event of free-ranging whitespotted eagle rays (Aetobatus narinari) in Brazilian waters. These observations shed light on utilizing the marine no-take zone surrounding the Anchieta Island State Park as a mating site in the South Atlantic region. Sightings of the species in shallower areas notably increased throughout summer months (from January to March, 2023 and from January to February, 2024), which aligns with its known reproductive period. Specifically, the mating event occurred in March 2023, followed by observations of courtship behavior in January 2024. While the population dynamics and impact of fisheries remain poorly understood, the species is frequently captured by traditional fishing fleets and traded locally. This reiterates the importance of the local Marine Protected Areas (MPAs) and underlines the urgency for their expansion, alongside the need for further studies that support specific management actions.
Keywords: Autecology; Citizen science; Elasmobranchs; Endangered species; Marine protected areas